2016
DOI: 10.1179/2042618615y.0000000007
|View full text |Cite
|
Sign up to set email alerts
|

In vivo measurements of humeral movement during posterior glenohumeral mobilizations

Abstract: Objectives: The purpose of this study was to quantify in vivo posterior translational movements occurring in the glenohumeral joint during posterior mobilizations and to determine the intratester reliability of those posterior translational movements. Methods: Twenty-eight individuals (17 females, 11 males) participated in this study. One physical therapist utilized a Kaltenborn approach to apply three grades of posterior humeral mobilization. A hand held dynamometer was used to quantify the force used during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
1
7
1
Order By: Relevance
“…In the study by López-de-Celis et al [22] the force intensity in low and medium force was lower than those in the present study, with values of 16.2 N ± 5.1 for grade I and 46.7 N ± 12.4 for grade II, whereas in the present study the applied force values were 22.4 N ± 3.8 and 68.0 N ± 9.6, respectively. However, for high force, a higher force was applied in the present study, with a difference of 57.8 N. We cannot compare this with the applied force in the study by Guerra-Rodríguez et al [32], who, with practically equal coracohumeral distraction distances, did not evaluate the applied force.…”
Section: Discussioncontrasting
confidence: 64%
“…In the study by López-de-Celis et al [22] the force intensity in low and medium force was lower than those in the present study, with values of 16.2 N ± 5.1 for grade I and 46.7 N ± 12.4 for grade II, whereas in the present study the applied force values were 22.4 N ± 3.8 and 68.0 N ± 9.6, respectively. However, for high force, a higher force was applied in the present study, with a difference of 57.8 N. We cannot compare this with the applied force in the study by Guerra-Rodríguez et al [32], who, with practically equal coracohumeral distraction distances, did not evaluate the applied force.…”
Section: Discussioncontrasting
confidence: 64%
“…US imaging has been shown to be a reliable measure of posterior translation of the humeral head during mobilization. 46 The transducer was oriented horizontally over the anterior shoulder visualizing the coracoid process, the lesser tuberosity, and the biceps tendon in the display. ( Figure 1 ) With the arm held in the GH resting position, a resting image was taken.…”
Section: Methodsmentioning
confidence: 99%
“…Several authors [17][18][19] reported that GHJ mobilization using loads of 20-80 N increased capsule extensibility or elongation and improved patient symptoms [20,21]. The proposed mechanical and neurophysiological changes responsible for increased joint ROM following joint mobilizations are not well understood and require further investigation [22]. Shear wave elastography (SWE) measurements are a reproducible method of evaluating muscle and tendon [23][24][25][26], with good repeatability, as demonstrated by intraclass coefficients (ICCs) of 0.81-0.91.…”
Section: Introductionmentioning
confidence: 99%